Penyuluhan dan Pendampingan Pendidikan Keluarga Berbasis Sekolah dalam Meningkatkan Ketahanan Sosial Masyarakat di Kota Palembang - Indra Gunawan; Melati Sari; Aditya Pramana Pramana; Reni Oktavia; Bayu Firmansyah; Siska Yuliana Yuliana; Ahmad Ridho (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2025)
The social resilience of communities in Palembang City faces complex challenges due to social changes and the weak role of family education. This research aims to analyze the effectiveness of school-based family education outreach and mentoring in enhancing community social resilience. The implementation method employs a participatory approach through outreach, training, and ongoing mentoring for 120 families across five elementary schools in Palembang over six months. The results show a significant increase in parents' understanding of character education (85%), improved family communication (78%), and increased parental involvement in children's education (82%). The program successfully built a community network of families concerned with education, which promotes social resilience through strengthening family values, social solidarity, and community participation. The conclusion indicates that school-based family education is effective in enhancing social resilience by involving a tripartite educational collaboration.